2019
DOI: 10.4236/ojst.2019.93005
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Age and Gender on Severity and Types of Periodontal Diseases among Patients from Two Regions in Saudi Arabia

Abstract: Background: Periodontitis is the predominant disease in the oral cavity and there are alterations in the periodontal tissues associated with the aging and gender of the patient. Objective: The present study was designed to assess the impact of age and gender of the patient on severity and types of periodontal diseases among patients from two regions in Saudi Arabia. Materials and Methods: The current study was done on 600 Saudi patients from Aseer and Tabuk regions in Saudi Arabia (50% males and 50% females) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…20 Significant difference was found between male and female according to BOP, the causes of these gender variations may be due to the fact that women before menstruation and during ovulation will have a rise in progesterone level, which in turn, prevents the reconditioning of collagen fibers leading to blood vessels widening. 21…”
Section: Discussionmentioning
confidence: 99%
“…20 Significant difference was found between male and female according to BOP, the causes of these gender variations may be due to the fact that women before menstruation and during ovulation will have a rise in progesterone level, which in turn, prevents the reconditioning of collagen fibers leading to blood vessels widening. 21…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies found that female gender is associated with increased severity and incidence of periodontal diseases and attributed that to the hormonal changes. 3,4 The mass of bacteria or biofilm that accumulates on the teeth surfaces within the mouth is called dental biofilm. It is a colourless, sticky mass that shortly converts to a pale yellow or brown deposit.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is not related to the physiologic or genetic differences between genders, but it may reflect better oral hygiene measures that are used by females than those used by males, as well as the years of puberty. However, some studies found that female gender is associated with increased severity and incidence of periodontal diseases and attributed that to the hormonal changes 3,4 …”
Section: Introductionmentioning
confidence: 99%